Development of palm methyl ester microemulsions as aerosol insecticides - Othman, Rohana (2015)
Palm methyl ester microemulsions are used as a basis for preparing aerosol insecticides against domestic insect pests due to their favourable characteristic such as renewable resources, biodegradable, non-flammable, and less or non-toxic to end users. The study focuses on the development of microemulsion-insecticides using palm-based materials as the oil phases, emulsifiers and/co-emulsifier, and apply them as a basis for preparing aerosol insecticides for household uses. The work includes utilization of palm-based materials containing mixed Tween 80 and Dehydol LS2 (Tween 80:DLS2) at ratios of 70:30, palm methyl esters (PME), deionized water (DH2O), and 1-propanol as a cosurfactant (Tween 80:DLS2/PME/DH2O/1-propanol) for preparing water in oil (W/O) and oil in water (O/W) microemulsion (μE) solutions. It involves screening process, ternary phase diagram study, physico-chemical characterizations of microemulsions, formulating and preparing microemulsion-insecticides as aerosol-insecticides, and bioefficacy test of the formulated products on insect pests. The optimum compositions and concentrations for both W/O-μE and O/W-μE solutions showed very clear appearance and thermodynamically stable at ambient and high temperatures (45ºC) as well as low in viscosity and very small particles with nano size. Ternary phase diagrams systems containing mixed Tween 80:DLS2/PME/DH2O/1-propanol showed large isotropic regions. The optimum compositions for W/O-μE solution were at the range of 20% mixed Tween 80:DLS2 (70:30); 20%-25% PME; 47.5%-40% DH2O; 12.5%-15% 1-propanol while for O/W-μE solutions, the optimum compositions were at the range of 7.5%-12.5% mixed Tween 80:DLS2 (70:30); 5%-7.5% PME; 77.5%-70% DH2O; 10% 1-propanol. Both systems were used to formulate W/O-μE and O/W-μE aerosol insecticides to control flying insects such as Aedes Aegypti mosquitoes and crawling insects such as Periplaneta Americana cockroaches respectively. The physical stability and the mist behaviour of the palm methyl esters aerosol insecticides were studied. There were very fine mist (30-50 microns) suspended longer in the air (6-8 seconds) observed with no water droplet released and no foam formation. These properties made them very suitable to be applied as flying insect killer (FIK) and crawling insect killer (CIK) aerosol-spray products. The bioefficacy test on both products showed good performance in knocking down insects by 100%, 24 hours of mortality rate as compared to the Malaysian Standard Aerosol. In conclusion, this system consisting mixed non ionics surfactants, PME, and non-toxic co-surfactant has great potential to be used in preparing palm methyl esters aerosol insecticides which are more environmental and end-users friendly.